Host switching is the main driver of coevolution between Hepatozoon parasites and their vertebrate hosts - Raúl Matamoros-Suárez; Víctor M. Montenegro; Federico Villalobos-Brenes; Mar Llaberia-Robledillo; Alberto Solano-Barquero; Gad Baneth; Juan Antonio Balbuena; Alicia Rojas (Parasites & Vectors)
Abstract Background Hepatozoon spp. are apicomplexan parasites with a heteroxenous life cycles, involving vertebrate intermediate hosts and invertebrate definitive hosts. These parasites infect a wide variety of wild and domestic vertebrates causing subclinical infection or mild-to-severe clinical manifestations, depending on the parasite species and vertebrate host. Interestingly, each Hepatozoon spp. have a specific host range, suggesting a close host–parasite coevolutionary relationship. Methods Hepatozoon sequences deposited between 2013 and 2023 were mined from GenBank to test which was the most employed marker for this parasite. We reconstructed the host and parasite phylogenies using 18S rDNA and cytB sequences, respectively. Subsequent analyses were stratified according to host vertebrate orders (Carnivora, Rodentia, and Squamata), and the corresponding sequences of their Hepatozoon parasites. Then, Procrustean Approach to Cophylogeny (PACo) and ParaFit were employed to assess their global cophylogenetic relationships. In addition, eMPRess was used to estimate the most probable co-evolutionary events, such as host switch, duplication, sorting, or cospeciation, accounting for the shared evolutionary history of Hepatozoon spp. and their vertebrate hosts. Results Global assessments of congruence between phylogenies of carnivore, rodent, and squamate hosts and those of their Hepatozoon parasites were significant (PACo: all m 2 XY < 0.655, all P < 0.001; ParaFit: all ParaFitGlobal Statistics < 72.992, all P < 0.007, all Procrustes R 2 > 0.25), but not for the association between Hepatozoon spp. and invertebrates (PACo m 2 XY = 0.632, P < 0.001; ParaFitGlobal Statistic = 8.810, P = 0.124, R 2 = 0.37). The most significant links occurred between Hepatozoon felis and felid hosts or Hepatozoon canis and canid hosts, but not between Hepatozoon americanum and domestic dogs or coyotes. Moreover, eMPRess showed that the coevolutionary history between Hepatozoon spp. and vertebrate host phylogenies was mainly explained by host switching and less frequently by cospeciation events. Conclusions These findings highlight the ability of Hepatozoon spp. associated to certain vertebrate orders to infect those with a close phylogenetic relationship. This in turn helps to understand how hepatozoonosis can emerge in susceptible hosts within specific geographical areas by spillover events. Graphical abstract